Eksistensi Bahasa Widal pada Masyarakat Tipar Sukabumi, Provinsi Jawa Barat: The Existence of Widal Language in Tipar Community, Sukabumi, The Province of West Java - Lilis Sukmawati (Kantor Bahasa Provinsi Maluku, 2022)
This study aims to determine and understand the existence of the Widal language in the Tipar Sukabumi community, West Java Province. This study used qualitative research methods. data obtained based on observations, interviews, and documentation. The location of the research was carried out in Sukabumi City, precisely in Tipar Sukabumi District, West Java Province. Determination of informants using purposive sampling, namely by interviewing informants who know and understand clearly the problems being studied. The results show that the existence of the Widal language in the Tipar community is still maintained until now thanks to the cooperation and cohesiveness that has been built in the Tipar community in maintaining the preservation of the language. Keywords: existence; widal language